Childhood Hodgkin Lymphoma in Sub-Saharan Africa: A Systematic Review on the Effectiveness of the Use of Chemotherapy Alone - Hellen Mugarra Kabahweza RN, BHSM, MME, MPH; Angela Spencer BSc, PGDip, SFHEA, PhD (SAGE Publishing, 2024)
Introduction. Childhood Hodgkin lymphoma (HL) is often curable, but in Sub-Saharan Africa (SSA), access to standard treatments like combined chemotherapy and radiotherapy is limited. This study aimed at evaluating the effectiveness of using chemotherapy alone for children with HL in SSA. Methods. We searched Medline, Embase, Cinahl Plus and Cochrane Central databases for records of studies that evaluated childhood HL survival outcomes from January 2000 to December 2022. Results. Six observational studies were identified for inclusion, and 3 were included in the meta-analysis. Most HL cases included in the analysis presented with lymphadenopathy and the nodular sclerosing subtype, with a high percentage (80%) in advanced stages. The GRADE certainty of the evidence for the assessed outcomes was rated as very low. Overall survival with chemotherapy was 67.8% (95% CI: 42.1%-88.8%). Conclusion. Chemotherapy is a potential treatment choice for childhood HL in SSA. However, it is crucial to approach this option cautiously due to the limited certainty of the supporting evidence. To improve outcomes for affected children in SSA, more robust studies are needed, along with a focus on early detection and supportive care.